Next Generation Access and Digital Divide: Opposite Sides of the Same Coin? - Cosimo Dolente; John Joseph Galea; Claudio Leporelli (International Telecommunications Society (ITS), 2010)
Geographical averaging of retail and wholesale prices could distort incentives for bypass entry in both the metropolitan and the high-cost areas. The two-instrument approach to universal service support, proposed in (Armstrong, 2001), could enhance efficiency, through competitive and technological neutrality. Alternatively, the industry support to high cost areas could be substituted by redistributive fiscal measures or public subsidies. Using evidence from Italy we suggest that tackling demographic, educational, and income inequalities is necessary, even in low cost areas, to support further broadband penetration. We estimate logistic regressions of Internet and broadband use at home, and show that a substantial increase of broadband penetration is possible in Italy only if specific platforms and applications are made available to older and less educated households. Therefore, a critical mass of services could help reaching the critical mass of users that make Next Generation Access Networks viable.
Keywords: L51; L96; 330; Infrastructural Digital divide; Cultural Digital Divide; Geographical crosssubsidies; Efficient bypass; Critical mass of services